2019
DOI: 10.1159/000494554
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Diarrhea Secondary to Newly Diagnosed VIPoma

Abstract: Vasoactive intestinal polypeptide-secreting tumors (VIPoma) are a rare pancreatic neuroendocrine tumor that can cause chronic diarrhea with 1 case per 10 million people per year. Diagnosis is made based on a combination of laboratory evaluation (serum VIP level), imaging findings (functional positron emission tomography-computed tomography [PET-CT]), and histological analysis (chromogranin A stain). We present a case of a male with 6 months of diarrhea and malaise who was found to have significant kidney injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
2
1
1
Order By: Relevance
“…The case of pancreatic VIPoma presented herein differs from other previously reported cases [9][10][11][12][13][14][15][16] in terms of the short duration and rapid progression of patient's symptoms before admission. The patient reported no similar symptoms in the past few months or intake of medications that could be responsible for diarrhea.…”
Section: Discussioncontrasting
confidence: 80%
“…The case of pancreatic VIPoma presented herein differs from other previously reported cases [9][10][11][12][13][14][15][16] in terms of the short duration and rapid progression of patient's symptoms before admission. The patient reported no similar symptoms in the past few months or intake of medications that could be responsible for diarrhea.…”
Section: Discussioncontrasting
confidence: 80%
“…La alta concentración de PIV produce una activación de la cAMP a nivel intracelular, produciendo en los enterocitos una secreción aumentada de electrólitos, seguida de su liberación, junto con agua, a la luz intestinal, lo que origina una diarrea profusa con hipovolemia, y en algunos casos, incluso una insuficiencia renal, que suele ser la causa más frecuente de muerte en tumores secretores de PIV (Farina et al, 2019;Ito & Jensen, 2021). Las alteraciones séricas de electrólitos son típicas del síndrome de WDHA.…”
Section: Tumores Secretores De Vipunclassified
“…The study demonstrated the high specificity of VIP levels in aiding the diagnosis of VIPomas. It is worth noting that other peptides, including gastrin and insulinoma, can also be elevated in patients with VIPomas [ 36 ].…”
Section: Diagnosis Of Functional Pannetsmentioning
confidence: 99%